'Are we opening a can of worms?': Community‐based occupational therapists' experiences working with clients with unexpected mental health issues. (5th January 2022) - King, Olivia; Ingwersen, Kate; Bufton, Brooke; Hitch, Danielle; Dupre, Brodie; Harding, Melita; Mayhew, Catherine; van de Ven, Sarah
Abstract: General community occupational therapists (OTs) work with clients experiencing chronic and complex conditions, some living with one or more comorbid common mental health issues (such as anxiety, depression or distress). This study aimed to describe the perspectives of general community OTs of their engagement with clients experiencing mental health issues; their perceptions of the implementation of routine screening in their practice, and the knowledge, skills and support they need to identify and support their clients' mental health needs. Six focus groups were undertaken with general community OTs ( n  = 21) from three Australian health services in rural, regional and metropolitan settings, between December 2020 and January 2021. Data were analysed using a team‐based framework approach. Three key themes were identified: (1) OTs' experiences working with people with mental health issues; (2) impacts of engaging with clients experiencing mental health issues on OTs; and (3) implementing routine mental health screening in general community OT practice. The latter had two sub‐themes: (i) identified considerations and (ii) education and system‐level support needs. General community OTs frequently work with clients with mental health issues. These experiences impact their practice in multiple ways. This study highlights opportunities for integrating routine mental health screening into general community OT practice and identifies the system and educational development required to support this enhancement to practice. Supporting general community OTs to routinely screen for mental health issues will enhance collaborative client‐centred care. Our findings may also have implications for other community‐based health professionals and services, particularly those delivered in clients' homes.